(untitled) (Journal of Engineering, 2026)
A hydraulic characteristic analysis was conducted to support the plan to construct the Cisangkuy River Weir in the Cikalong Hydroelectric Power Plant area, aiming to improve the fulfilment of raw water needs entering the inlet system of the South Bandung Regional Water Company. The main problem faced is the seasonal discharge fluctuations and watershed degradation, which cause the intake discharge during the dry season to only reach 0.09 m3/s, far below the minimum requirement of 0.7 m3/s. This study uses a research methodology that includes hydrological data collection, river cross-section surveys, and hydraulic modeling using HEC HMS and HEC-RAS 1D version 6.3.1 software. The simulation results show that the construction of a weir height of 1 m and a width of 1.5 m with a sluice gate system can significantly increase the intake flow rate. In dry conditions, the optimal flow rate reaches 0.62 m3/s without downstream flow, if the hydroelectric power plant operates and the gate is opened 0.1 m, the flow inlet conditions will be 0.55 m3/s with a downstream inflow of 4.69 m3/s. In the rainy season, optimal conditions are achieved at a return period of 2-5 years by fully opening the two weir gates so that the water surface elevation does not exceed the peak of the hydroelectric power plant (+885.5 m) with an inflow discharge between 0.51 and 1.20 m3/s. The integration of the weir with adaptive sluice gates has proven effective in ensuring the sustainability of raw water supply while mitigating flood risks.